Trust and the rule of law - Simpson, TW (Oxford University Press, 2024)
This chapter is interested in the conditions that sustain the rule of law. It is argued that there is a reciprocal relationship between the rule of law and trust. The rule of law promotes a culture of trust, while a culture of trust promotes the rule of law. Conversely, the absence of the rule of law undermines a culture of trust, and a culture of distrust inhibits and undermines the rule of law. The reciprocal relationship has significant normative implications. Because trust is an independent influence on the rule of law, protecting the sources of social trust is a goal of both law and policy, and one that may trade off against that of social justice.